Hormone receptor status influences the impact of body mass index and hyperglycemia on the risk of tumor relapse in early-stage HER2-positive breast cancer patients. (April 2021) - Ligorio, Francesca; Zambelli, Luca; Bottiglieri, Achille; Castagnoli, Lorenzo; Zattarin, Emma; Lobefaro, Riccardo; Ottini, Arianna; Vingiani, Andrea; Pupa, Serenella M.; Bianchi, Giulia V.; Capri, Giuseppe; Pruneri, Giancarlo; et al.
Background: High body mass index (BMI) has been associated with worse clinical outcomes in patients with early-stage breast cancer (BC), and its negative effects could be mediated by hyperglycemia/diabetes. However, the prognostic impact of high BMI in early-stage HER2-positive (HER2+) BC patients remains controversial. Methods: We conducted a retrospective study to investigate the impact of baseline BMI or glycemia on relapse-free survival (RFS) and overall survival (OS) in patients with surgically resected, stage I–III HER2+ BC treated with standard-of-care, trastuzumab-containing adjuvant biochemotherapy. The optimal BMI and glycemia cut-off values for RFS were identified through maximally selected rank statistics. Cox regression models were used to assess the impact of BMI, glycemia and other relevant variables on clinical outcomes. Results: Among 505 patients included in the study, a BMI cut-off of 27.77 kg/m 2 was identified as the best threshold to discriminate between patients with low BMI ( n  = 390; 77.2%) or high BMI ( n  = 115; 22.8%). At multivariable analysis, higher BMI was associated with significantly worse RFS [hazard ratio 2.26; 95% confidence interval (CI): 1.08–4.74, p  = 0.031] and worse OS (hazard ratio 2.25, 95% CI 1.03–4.94, p  = 0.043) in the whole patient population. The negative impact of high BMI was only observed in patients with hormone receptor (HR)-negative/HER2+ BC (hazard ratio 2.29; 95% CI: 1.01–5.20; p  = 0.047), but not in patients with HR-positive (HR+)/HER2+ BC (hazard ratio 1.36; 95% CI: 0.61–3.07, p  = 0.452). By contrast, hyperglycemia (⩾109 mg/dl) at baseline was associated with a trend toward significantly worse RFS at multivariable analysis only in patients with HR+/HER2+ BC (hazard ratio 2.52; 95% CI: 0.89–7.1; p  = 0.080). Conclusions: High BMI is associated with worse clinical outcomes in early-stage HR−/HER2+ BC patients treated with trastuzumab-containing adjuvant biochemotherapy, while baseline hyperglycemia could be a predictor of worse RFS in HR+/HER2+ BC patients. Prospective studies are needed to investigate if modifying patient BMI/glycemia during treatment can improve clinical outcomes.